Exotic Pets as a Vector for Leptospirosis: An Original and Difficult to Prove Mode of Transmission. Issue 4 (July 2020) - Lacombe, Valentin; Landais, Mickaël; Urbanski, Geoffrey; Callahan, Jean-Christophe
Abstract : Abstract: Leptospira propagate via urine shedding by carrier animals with chronic renal infestation, particularly rodents. The growing trend of exotic pet ownership may increase the incidence of leptospirosis and lead to a new mode of transmission. We report a case of human leptospirosis whose highly suspected vector was a domestic ferret. Careful questioning did not reveal any recent usual context of leptospirosis transmission in our patient, and the only vector found was his pets, which had been in contact with rodents in previous years. Urinary sampling is technically difficult in ferrets, and the bacterial shedding is intermittent, so the evidence of chronic carriage in exotic pets is rarely reported. To be aware that exotic pets are a potential source of infection is important to suspect this polymorphic disease. The exposure to contaminated water or rodents by the pet, even several years prior, should lead to suspect leptospirosis.